(untitled) (Annals of Medical Research, 2021)
Aim: Children requiring intensive care in the neonatal period have more fine motor injuries, learning difficulties, eating disorders and sleeping problems. Sleep disorder rate is about 10-30% in children who had no problem in newborn period. We aimed to investigate the rate of sleep disorder in children who were hospitalized in the neonatal intensive care unit during the neonatal period. Material and Methods: Fourty-six patients hospitalized in neonatal intensive care unit and still followed in outpatient policlinic at Çukurova University were enrolled in to the study. Children’s Sleep Habits Questionnaire was performed to evaluate sleep resistance, delay in fall into sleep, duration of sleep, sleep anxiety, parasomnia, midnight awakening and daily sleepiness.Results: Children were 6.64±1.18 years old. They were healthy and had no neurological sequela. None of the parents complained about sleep disorders. However, 20 of the 46 (43.47%) children had sleep disorder (Sleep disorder group). Twenty-six children had no sleep disorder (No sleep disorder group). There isn’t any statistically difference between the groups that terms of gestational age, birth weight, ventilator support, gender (p>0.05).Conclusion: Although there isn’t any significant difference between groups, sleep disorder rate is higher compared to normal population’s rates reported in the previous studies. Infants discharged from neonatal intensive care unit should be under evaluation also for sleep disorder.